Below Stairs : The Bestselling Memoirs of a 1920s Kitchen Maid - Powell, Margaret (London Pan Book, 2011)
Below Stairs' is a compelling and colourful memoir that takes the reader inside the upstairs downstairs world of domestic service.
Keywords: Great Britain -- Cooks -- Working class women